ELABORACIÓN DE UN EMPAQUE BIODEGRADABLE CON MATERIAL ORGÁNICO A PARTIR DE ALMIDONES Y PECTINAS: ELABORATION OF A BIODEGRADABLE PACKAGING WITH ORGANIC MATERIAL FROM STARCHES AND PECTINS - Orduz Carrillo, Ana Gabriela
The project carried out an evaluation of seven Tahiti lemon patterns (Krayder 3015, CPB Citrum, Cleopatra Mandarin, Volkamerian Orange, Troyer, Flying Dragon, Sunky and English) at La Reina farm, located in the Versailles village at an altitudeof 1330 meters above sea level. The main purpose of this study was to record the performance of their growth under field conditions over a period of six months and offer recommendations to local producers on which Tahitian lemon pattern of the seven analyzed could offer the best yield, considering the specific conditions of the region, documenting the establishment ofthe seven lemon patterns according to good agricultural practices from the nursery phase to the sixth month after planting. Measurements were made of variables such as plant height, stem diameter and number of branches. The results concluded that, among the varieties analyzed, those that presented a higher yield in terms of growth and development were Volkamerian and Troyer. These two varieties demonstrated significant values in all the growth variables that were evaluated.